Analyse D’une Poche De Précarité En Milieu Rural : Exemple Du Quartier Allogène De Songon-Agban (Côte d’Ivoire) - Odilon, Assi Akotto Urich; Jerome, Aloko-N’guessan (European Scientific Journal, ESJ, 2018)
This article raises the problem of residential precariousness in Songon-Agban. Indeed, the evolution of the foreign population of Songon- Agban, favored the development of a pocket of precariousness on a part of the village territory whereas the economic dynamics which this village knows contributed however to the improvement of the framework of life of the village nucleus. As a result, this study seeks to highlight the socio-demographic, spatial and environmental characteristics of this pocket of precariousness. In addition, it identifies the factors that limit the restructuring of this area marked by residential precariousness (allogeneic space). The methodology adopted to conduct this study was based on direct observation of residential areas occupied by non-Aboriginal people, the inventory of socio-collective facilities present in this area and a questionnaire survey administered to selected households. To this end, we interviewed 361 randomly selected households. The results revealed that more than 65% of the dwellings in this neighborhood are fortunate shelters built with recycled materials, sheet metal, planks or dirt. This studied area is marked by a promiscuity of housing and sanitation problems. This study also indicated that more than 70% of residents had access to illegal home electrification while nearly 60% of them had problems with access to drinking water